2003
DOI: 10.1208/ps050222
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sucrose esters as alternative surfactants in microencapsulation of proteins by the solvent evaporation method

Abstract: KEYWORDS: proteins, microencapsulation, solvent evaporation, sucrose ester, surfactants Sucrose esters (SE) are surfactants with potential pharmaceutical applications because of their low toxicity, biocompatibility, and excellent biodegradability. The objective of the study was to investigate SE as alternative surfactants in stabilizing emulsions for the preparation of protein-loaded microparticles. To achieve this goal, using bovine serum albumin as model protein and 75/25 poly(d,l-lactide-co-glycolide) as po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 24 publications
(26 reference statements)
0
21
0
Order By: Relevance
“…This is explained by the low CMC value of lutrol F 68 (0.1%) (22) and Tween 80 (0.0013%) (23). In general, at the same concentration, mean size of nanoparticles was in the order of PVA > lutrol F 68 > Tween 80.…”
Section: Preparation Of Blank Nanoparticlesmentioning
confidence: 94%
“…This is explained by the low CMC value of lutrol F 68 (0.1%) (22) and Tween 80 (0.0013%) (23). In general, at the same concentration, mean size of nanoparticles was in the order of PVA > lutrol F 68 > Tween 80.…”
Section: Preparation Of Blank Nanoparticlesmentioning
confidence: 94%
“…Microemulsions based on nonionic emulsifiers have been extensively investigated for their formulation, phase behavior, structural point of view, and also for the oxidation stability of the oil (Azuma et al, 2009;Tual et al, 2006;Takaishi et al, 2006). Youan et al (2003) reported an increasing interest in using SE in the microencapsulation process for stabilizing emulsions. Kwak et al (2001) reported that polyglycerol monostearate could be used as an effective coating material to microencapsulate lactase using an airless paint sprayer.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the study was to investigate SE as alternative surfactants in stabilizing emulsions for the preparation of protein-loaded microparticles (Youan, Hussain, and Nguyen 2003). Design and synthesis of new biodegradable and biocompatible polymeric hydrogel systems based on suger-containing monomers was the primary objective in our study.…”
Section: Resultsmentioning
confidence: 99%